AB0593 Disease Activity and Quality of Life in BehÇEt's Disease: the Role of Patients Reported Outcomes. (10th June 2014) - Talarico, R.; Elefante, E.; Stagnaro, C.; Ferrari, C.; d'Ascanio, A.; Tavoni, A.; Tani, C.; Baldini, C.; Mosca, M.; Bombardieri, S.
Abstract : Background: Behçet's disease (BD) is a systemic vasculitis, typically characterised by recurrent oro-genital ulcers, ocular inflammation and skin manifestations; articular, vascular, gastro-enteric and neurological involvement may also occur. Since BD has a chronic-relapsing course and it can be very severe, debilitating and potentially life-threatening, it may without any doubt affect the quality of life of the patients. Moreover, it is well known that patient's perception of own disease represents an useful tool to help physicians to improve the understanding and management of the disease itself. Objectives: The primary aim of this study was to explore the role of quality of life patients reported outcome (PRO) in better identifying the global status of BD. Methods: The study enrolled 120 patients, all fulfilling the International Study Group (ISG) criteria for BD. The male/female ratio was 1.6:1, with a mean disease duration of 11±6 years. Their mean age was 42±8 years (min:18, max:77), while the mean age at disease onset was 24±5 years. The primary end-point was to study any potential correlation between quality of life and disease activity. Disease activity was evaluated by means of the Behçet's Disease Current Activity Form (BDCAF), while the Italian version of the Short-form-36 (SF-36) was used to evaluate quality of life. Disease activity was compared with the global SF-36 score and with each dimension, that includes: physical functioning, physical disability, body pain, general health, vitality, social functioning, emotional disability, mental health. The statistical analysis was performed using Student t-test, Mann-Whitney-U test, ANOVA and Pearson correlation Results: At time of evaluation, according BDCAF, 47 BD patients (39%) had clinically active disease (18 ocular involvement, 8 joint involvement, 4 neurological involvement, 2 gastro-enteric, 15 muco-cutaneous involvement). As expected, the overall SF-36 scores were significantly lower in patients with clinically active disease. Moreover, female BD patients had statistically significant lower scores in all SF-36 domains compared with male patients. When each domain of SF-36 was evaluated, we found that physical disability (p=0.004), body pain (p=0.006), general health (p=0.001), and vitality (p=0.001) were significantly lower in patients with disease activity. Notably, vitality (p=0.001), physical disability (p=0.004), social functioning (p=0.001), emotional disability (p=0.003) and mental health (p=0.001) were significantly lower in patients with muco-cutaneous active disease, compared with the other patients with active disease. Conclusions: The clinicians who take care of any chronic disease would like to correctly know the current status of a patient to manage him properly. In this regard, the combination data of PRO measures and disease activity have been demonstrated to add more information compared to the evaluation of disease activity alone. These consideration suggest that the correct assessment of BD need a multi-dimensional approach, that fairly includes disease activity, disease damage and quality of life Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5715